Smart responsive organic microlasers with multiple emission states for high-security optical encryption - Gao, Zhenhua (Natl Sci Rev, 2020)
Modern high-security cryptography and optical communication call for covert bit sequences with high coding capacity and efficient authentication. Stimuli-responsive lasing emissions with easily distinguishable readout are promising in the coding field as a novel cryptographic primitive, while the application is frequently restricted by the limited number of emission states. Here, we report a strategy of achieving multiple competitive lasing signals in responsive organic microspheres where a donor–acceptor pair was introduced. The competitive lasing from the donor and acceptor was reversibly switched by modulating the competition between the radiative rate of the donor and the rate of energy transfer, and the generated multiple lasing signals enabled a quaternary coding for recognizable cryptographic implementation. Data encryption and extraction were demonstrated using a 4 × 4 microlaser array, showing vast prospects in avoiding the disclosure of security information. The results offer a comprehensive understanding of excited-state dynamics in organic composite materials, which may play a major role in high-security optical recording and information encryption.